2017
DOI: 10.1159/000484612
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Case of Cholestasis in a Patient with ABCB4 and ABCB11 Mutations

Abstract: The low-phospholipid-associated cholelithiasis (LPAC) syndrome is a form of symptomatic cholelithiasis occurring in young adults, characterized by recurrence of symptoms after cholecystectomy and presence of hepatolithiasis. The case refers to a healthy 39-year-old Caucasian male who presented with abdominal pain and jaundice. His blood tests showed conjugated hyperbilirubinemia and elevated liver enzymes (total bilirubin 6.65 mg/dL, γ-glutamyltransferase 699 IU/L) and abdominal computed tomography revealed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…There are only a few reports of such combined mutations in the literature. A similar digenic variation has been reported earlier by Cardoso et al ( 9 ) in a 39-year-old Caucasian male with choledocholithiasis, hepatolithiasis, and persistent conjugated hyperbilirubinemia after retrieval of stones. The patient fulfilled the criteria for LPAC syndrome and responded to UDCA therapy.…”
Section: Discussionsupporting
confidence: 88%
“…There are only a few reports of such combined mutations in the literature. A similar digenic variation has been reported earlier by Cardoso et al ( 9 ) in a 39-year-old Caucasian male with choledocholithiasis, hepatolithiasis, and persistent conjugated hyperbilirubinemia after retrieval of stones. The patient fulfilled the criteria for LPAC syndrome and responded to UDCA therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, isolated cases of patients with hepatitis delta have shown that AIH is also observed after treatment with pegylated interferon[ 18 ]. In contrast, a case of HDV-RNA flare has been reported in a previously negative patient who received immunosuppressive treatment for AIH[ 5 ].…”
Section: Aih Induced By Hdvmentioning
confidence: 99%
“…Many clinical studies have shown that HDV infection most often causes progressive liver disease more rapidly than other viral hepatitis, leading to liver cirrhosis in 70% of cases within 5 to 10 years[ 3 ]. Furthermore, HDV is independently associated with an increased risk of hepatocellular carcinoma (HCC) than hepatitis B virus (HBV) monoinfection[ 4 ] and has been associated with the development of autoimmune hepatitis (AIH), as in the serum of HBV/HDV co-infected patients, positive autoantibodies have been detected, and autoimmune features have been reported[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A case of DIC during ciprofloxacin therapy was described in a subject with LPAC, carrier of ABCB4 -related c.1954A>G (p.R652G), a homozygous missense mutation, already described in PFIC3 and ICP, combined to p.V444A in the ABCB11 gene in a heterozygous state [ 101 ].…”
Section: Canalicular Efflux Transport Proteins and Compounds Involved...mentioning
confidence: 99%